2016
DOI: 10.3389/fpls.2016.01336
|View full text |Cite
|
Sign up to set email alerts
|

Role of Proteomics in Crop Stress Tolerance

Abstract: Plants often experience various biotic and abiotic stresses during their life cycle. The abiotic stresses include mainly drought, salt, temperature (low/high), flooding and nutritional deficiency/excess which hamper crop growth and yield to a great extent. In view of a projection 50% of the crop loss is attributable to abiotic stresses. However, abiotic stresses cause a myriad of changes in physiological, molecular and biochemical processes operating in plants. It is now widely reported that several proteins r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 174 publications
(251 reference statements)
0
44
0
1
Order By: Relevance
“…and CA2 are involved in photosynthesis, and are usually depressed under drought stress in plants [10], and have a great effect on photosynthesis and water use efficiency [31]. Overexpression of CA1 or CA4 decreased stomatal density and improved water use efficiency [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and CA2 are involved in photosynthesis, and are usually depressed under drought stress in plants [10], and have a great effect on photosynthesis and water use efficiency [31]. Overexpression of CA1 or CA4 decreased stomatal density and improved water use efficiency [31].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the study of proteomics is an approach that could be used to discover proteins and pathways associated with crop physiological and stress responses [10]. Analyses of the soybean leaf proteome have been used to identify the differential expression of various abiotic stressresponsive proteins that regulate many molecular processes and signaling cascades [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The advancement of mass spectrometry-based proteomics has enabled the routine measurements of thousands of proteins in terms of their abundance, localisation, interactions, and modifications while connecting the large-scale data to gene expression regulation and function [ 89 , 90 ]. Targeted and untargeted proteomics experiments have been widely used to investigate crop responses to the abiotic stress [ 89 , 90 , 91 , 92 ]. Proteomics studies have shown that plant-derived smoke water solutions can improve the abiotic stress tolerance capacity in soybean [ 3 ], chickpea [ 93 ] and rice [ 36 ].…”
Section: Application Of Proteomics To Understand Smoke Water-assismentioning
confidence: 99%
“…Understanding the dynamic state of protein abundance and localization, protein–protein and protein–nucleotide interactions or post‐translational modification provides vital clues to explain cellular functionality and its regulation. While proteomics has played an important role in our understanding of plant stress responses under different conditions (Gong et al ., ; Ahmad et al ., ), it has not yet been widely applied to study biosynthesis of secondary metabolites and their regulation in non‐model medicinal plants.…”
Section: Omics Toolsets and Analysis To Discover Unknownsmentioning
confidence: 99%